Resistencia, negociación y cocreación de saberes para la construcción del Fondo Plurinacional del Agua en el territorio Kayambi, Ecuador: Resistance, negotiation and co-creation of knowledge for the construction of the Plurinational Water Fund in the Kayambi territory, Ecuador - Dupuits, Emilie (2023)
On a global scale, international experts produce knowledge about ecosystem services, often associated with techno-scientific visions of water resources. At the local level, these visions often compete with demands for water justice and local or traditional knowledge, defended by grassroots movements. This analysis is based on a case study in the Cayambe region, in the northern highlands of Ecuador, where the Confederation of the Kayambi People proposed in 2018 the creation of the Plurinational Water Fund. The study proposes a transdisciplinary approach combining qualitative and quantitative methods, including semi-structured interviews, surveys, focus groups, and water quality measurements. One of the main results of the study shows the complexity of the interactions and resistance in the co-production of water services between indigenous communities, local and municipal governments, the national government and private companies, within the framework of the creation and negotiation of the Plurinational Water Fund.